Educational foundations : philosophical and historical perspectives - Dotts, Brian W. (Cambridge, United Kingdom : Cambridge University Press, 2019)
This educational foundations book offers a comprehensive overview of American education history and a variety of classical, Enlightenment, and contemporary educational philosophers. The text is intended to provide educational foundations students with a solid grounding in philosophy and history as it relates to their academic discipline.
Introduction: Understanding social foundations of education -- Part. 1. Philosophy of education -- Part. 2. History of American education -- Index.
Includes bibliographical references.
Keywords: EDUCATION PHILOSOPHY